Child language - Peccei, Jean Stilwell (Language workbooks., 1999)
Building on the established strengths of the first edition, Child Language has now been fully updated and includes some basic theory content, more exercises and summaries at the end of each unit. Child Language:* introduces students to key areas involved in the study of children's language: vocabulary development, word and sentence structure, conversational skills and pronunciation* contains a corpus of children's language* includes suggestions for project work.